Role of the Salt Marsh Grass Spartina alterniflora in the Response of Soil-Denitrifying Bacteria to Glucose Enrichment - Sherr, B. F. (1979)
Long-term incubations of salt marsh soil systems in the presence of glucose resulted in a decrease in the soils' denitrification potential. Addition of nitrate or the presence of living Spartina alterniflora reversed this effect, indicating that Spartina, through the establishment of an oxidized rhizosphere where nitrification can occur, enables the denitrifying bacteria to adequately compete with the less energetically efficient components of the anaerobic soil microbial community.